Mitchie Kellogg: capstone - Kellogg, Mitchie, artist (Colorado State University. Libraries, 2024)
The artist's statement: Over the past year and a half, I have experienced true unfiltered grief for the first time. Since experiencing my first funeral last August, I have attended a total of five. Each were the ages of 20, 23, 29, 74, and 95. Every funeral was traumatic in its own right and taught me how special it is to be truly alive while we are here, and how much of an impact we all leave on each other without recognizing it. In lieu of these experiences, my recent series explores my reflections on grief through hand woven cloth, cyanotype, and Sashiko embroidery. I was recently able to spend time abroad in Japan, and my experience of the art and culture associated with spirituality and the balance of light and dark taught me so much about grief and has had a large influence on my work. I learned a new perspective on death and loss through studying and reflecting on the Japanese aesthetic world view of wabi sabi, and I express this through my use of Sashiko embroidery. Sashiko is a type of Japanese embroidery that uses a running stitch with white thread to strengthen a piece of fabric, and is seen consistently throughout my work as a way to add and take away from the images. Much like the cyanotype process which can be seen throughout my latest work, grief is the image that emerges from absence, and you can see and appreciate what you love more clearly after experiencing loss. Over time I reflected and realized that grief had always been present, just in different ways which weren't always specific to people. I grieve my childhood, the few years of innocence I experienced, and relationships with my family, especially with my mother. I grieve so many could've-beens for if this or that happened instead, but true loss has made me recognize how special my experiences are to me as a human being. Loss makes the present shine brighter, and brings meaning to experiences we each have. I represent myself in my work as the hand woven cloth that these images are printed upon, the memories and experiences which have shaped my being and the way I interact with the world and my communities. Although there is grief and mourning for what has been lost, there is also the deep appreciation for having experienced life at all when you have seen lives ended far too soon and lives that had been filled to their end. This appreciation is what creates the image of what I see in the present.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers